Quantifying progression in primary progressive aphasia with structural neuroimaging. Issue 10 (30th March 2021) - Lombardi, Jolina; Mayer, Benjamin; Semler, Elisa; Anderl‐Straub, Sarah; Uttner, Ingo; Kassubek, Jan; Diehl‐Schmid, Janine; Danek, Adrian; Levin, Johannes; Fassbender, Klaus; Fliessbach, Klaus; Schneider, Anja; et al.
Abstract: Introduction: The term primary progressive aphasia (PPA) sums up the non‐fluent (nfv), the semantic (sv), and the logopenic (lv) variant. Up to now, there is only limited data available concerning magnetic resonance imaging volumetry to monitor disease progression. Methods: Structural brain imaging and an extensive assessment were applied at baseline and up to 4‐year(s) follow‐up in 269 participants. With automated atlas‐based volumetry 56 brain regions were assessed. Atrophy progression served to calculate sample sizes for therapeutic trials. Results: At baseline highest atrophy appeared in parts of the left frontal lobe for nfvPPA (–17%) and of the left temporal lobe for svPPA (–34%) and lvPPA (–24%). Severest progression within 1‐year follow‐up occurred in the basal ganglia in nfvPPA (–7%), in the hippocampus/amygdala in svPPA (–9%), and in (medial) temporal regions in lvPPA (–6%). Conclusion: PPA presents as a left‐dominant, mostly gray matter sensitive disease with considerable atrophy at baseline that proceeds variant‐specific.